The antitumor effect of diisopropylamine dichloroacetate on non-small cell lung cancer and its influence on the tumor immune microenvironment - Wei, Min; Shen, Xiaoyan; Liu, Ye; Chen, Xiaotong; Su, Shu; Lv, Xin; Qian, Xiaoping; Yu, Lixia; Wang, Lifeng (Frontiers in Oncology, 2024)
ObjectiveTo evaluate the antitumor effects of diisopropylamine dichloroacetate (DADA) alone or in combination with chemotherapy/radiotherapy/immunotherapy in NSCLC and explore the underlying mechanisms involved.MethodsMTT, UV spectrophotometry, flow cytometry, fluorescence microscopy, and clonogenic survival assays were used. In LLC mouse models, the antitumor effects of radiotherapy, DADA, and the anti-PD-1 antibody alone or in combination were evaluated, and the T cell numbers were evaluated in different groups.ResultsDADA significantly inhibited lactate production and promoted apoptosis in NSCLC in vitro. Compared with pemetrexed or DADA alone, the combination of DADA with pemetrexed significantly inhibited proliferation and promoted apoptosis (p<0.05). This may be related to the decrease in the mitochondrial membrane potential in the combined group. Moreover, compared with radiotherapy alone, the combination of DADA with radiotherapy induced remarkable DNA damage. In vivo, the combination of radiotherapy, an anti-PD-1 antibody and DADA resulted in superior tumor inhibition than the combination of radiotherapy and anti-PD-1 antibody did (p < 0.05). The underlying mechanism may be partially related to the increased number of CD3+ T cells in the triplet combination group (p < 0.05).DiscussionOur results showed that DADA has strong antitumor effects on NSCLC, either alone or in combination with chemotherapy or radiotherapy. Interestingly, the combination of radiotherapy, anti-PD-1 antibody and DADA had a more pronounced tumor-suppressing effect, which may be related to DADA-induced T-cell generation by reducing local lactic acid production in the tumor microenvironment. This study lays the foundation for further exploration of DADA in lung cancer, especially in the era of immunotherapy, on the basis of its possible immunomodulatory effects.